Eco-friendly method of biocementation for soil improvement and environmental remediation in the context of Viet Nam: a state-of-the-art review - Nguyen, Ngoc Tri Huynh; Nguyen, Pham Huong Huyen; Nguyen, Hoang Thien Khoi; Nguyen, Khanh Son (Vietnam Journal of Science and Technology, 2023)
Scientists have been using microorganisms to improve soil strength and durability through a process called biocementation. This technique involves inducing mineral precipitation to form a cement-like material that enhances soil properties. Biocementation has been successful in various applications, including soil stabilization, erosion control, and groundwater remediation. Researchers are optimizing nutrient concentrations and ratios to create a favorable environment for microbial activity and promote efficient mineral formation. Different microorganisms have varying abilities to induce mineralization, and cycle treatments have shown promise in stimulating biomineralization processes. Biocementation is a sustainable and eco-friendly technique that can stabilize and immobilize contaminants in soil and groundwater, preventing the spread of pollutants. Despite these challenges, biocementation holds great potential for innovative soil improvement and environmental remediation. Recent studies, experiments, testing devices, and results from research groups in the world and Vietnam in recent years were reviewed to gain insight into this promising approach. Ongoing research aims to develop cost-efficient and sustainable methods for large-scale production and application of biocementing agents. Further research is needed to uncover the intricate mechanisms and identify optimal strategies for applications and environmental conditions.